Learner Diversity in Science Education: Auditory and Kinesthetic Preferences within a Holistic Islamic Education Perspective - Mukhlis; M. Yusuf; Nuzliah; Ainul Mardhiah (Al-Mudarris, 2026)
Learner diversity is a fundamental issue in contemporary education and Islamic educational thought, which recognizes individual differences as part of human fitrah that must be developed through tarbiyah, guided through ta’lim, and refined through ta’dib. In science education, learner diversity is often discussed from psychological and instructional perspectives, while its interpretation within Islamic educational philosophy remains limited. This study aims to examine the relationship between auditory and kinesthetic learning preferences and students’ science achievement within an integrative perspective of Islamic education. A quantitative correlational design was employed involving 31 grade XII students at SMAN 1 Mutiara Beureunun, Indonesia. Data were collected using a learning preference questionnaire and a science achievement test, and analyzed using Pearson Product Moment correlation. The results indicate a moderate and significant positive correlation between kinesthetic learning preference and science achievement (r = 0.483; p = 0.006), while auditory learning preference shows a very weak and non-significant relationship (r = 0.121; p = 0.518). These findings suggest that experiential and hands-on learning contributes more strongly to science achievement than passive receptive learning. From the perspective of Islamic education, these results reflect learner diversity as a manifestation of fitrah that requires continuous educational guidance through integrated processes of tarbiyah, ta’lim, and ta’dib. Therefore, learning preferences should be understood as descriptive variations in learner engagement that need to be accommodated through differentiated and holistic instructional approaches in science learning.